Defect pair formation in FAPbI3 perovskite solar cell absorbers - DEĞER, CANER; YAVUZ, İLHAN (My University, 2022)
© 2022 American Chemical Society.Formamidinium lead iodide (FAPbI3) based hybrid perovskite light absorbers have shown remarkable performance in recent years. Since they have unique set of optoelectronic characteristics, they are considered as a good candidate absorber material for future solar cell applications. Until recently, much research had focused on the quantitative analysis of point defects on halide-based perovskite solar cells. Studies show that understanding defect mechanisms in perovskites has a huge impact on efficiency and stability improvements; however, such mechanisms have not been fully understood yet. Here, using first-principles calculations, we investigate the possible defect pair formations in FAPbI3, characterized by their formation energies and charge transitions. We found that while some donor and acceptor point defects are unstable and shallow when they are isolated, they form stable and deep-trap defect pairs and potentially limit the optoelectronic performance. We anticipate that our results will influence future discussions on the impact of defect formation on the performance and stability of perovskite solar cells.
Keywords: Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, FİZİKSEL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, PHYSICAL; Genel Malzeme Bilimi; Fizik Bilimleri; Fiziksel ve Teorik Kimya; General Materials Science; Physical Sciences; Physical and Theoretical Chemistry